Pengembangan Cognitive Flexibility Inventory dengan Analisis Pemodelan Rasch - Rohman, Yuni Nur; Adiwinata, Anne Hafina; Saripah, Ipah; Ahman, Ahman (Universitas Muhammadiyah Metro, 2025)
The Cognitive Flexibility Inventory (CFI) is a short 20-item self-report questionnaire that can be used to measure individual cognitive flexibility in thinking adaptively to an ever-changing environment. This study aims to develop a cognitive flexibility inventory instrument in the Indonesian context and test the instrument using Rasch modeling analysis. The research method used was a survey with a cross-sectional survey design. The research sample was 170 students of Universitas Pendidikan Indonesia. The research instrument used is the Cognitive Flexibility Inventory (CFI) adapted from Dennis & Vander Wal (2010) and has been translated from English to Indonesian. The results showed that the development of the Cognitive Flexibility Inventory (CFI) instrument based on Rasch modeling analysis has excellent instrument reliability with a Cronbach alpha value of 0.87 logits, and CFI can measure what should be measured in this study, namely cognitive flexibility in students. For this reason, the development of the CFI instrument in Indonesian produced good results and has the potential to be widely implemented in the university environment.